Delo službe za fizikalno in rehabilitacijsko medicino v sb celje med epidemijo COVID-19 - Plaskan, Lidija (Rehabilitacija (Ljubljana), 2021)
COVID-19 poses a challenge to the whole health care, including rehabilitation. In the majority of cases, the disease course is mild, but intensive care unit (ICU) treatment is required in approximately one fifth of the patients. It is a respiratory infection with multisystem manifestations (neurological, musculoskeletal and psychological). Rehabilitation is an essential part of COVID-19 patient management, in the acute phase as well as in the long term. The rehabilitation models vary between hospitals in accordance with the patients% needs. In the Celje General Hospital we intensified rehabilitation services mainly in the ICU and in the infection ward; it has also been introduced in the newly established COVID wards. Pulmonary rehabilitation is essential for survival and final outcome. It is currently provided only for the hospitalised patients. Because of long-term decrease in pulmonary function, it will have to be implemented at the outpatient level in primary care, where other rehabilitation services will also have to become more accessible.
Keywords: COVID-19; organizacija dela; rehabilitacija; Rehabilitation; work organisation